2016
DOI: 10.1128/mbio.00029-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Upregulates the Mitochondrial Transcription and Translation Machineries

Abstract: Infection with human cytomegalovirus (HCMV) profoundly affects cellular metabolism. Like in tumor cells, HCMV infection increases glycolysis, and glucose carbon is shifted from the mitochondrial tricarboxylic acid cycle to the biosynthesis of fatty acids. However, unlike in many tumor cells, where aerobic glycolysis is accompanied by suppression of mitochondrial oxidative phosphorylation, HCMV induces mitochondrial biogenesis and respiration. Here, we affinity purified mitochondria and used quantitative mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 115 publications
6
54
0
Order By: Relevance
“…8). These data are consistent with previous reports showing increased mitochondrial biogenesis and upregulation of mitochondrial transcription and translation pathways (39,42,54).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…8). These data are consistent with previous reports showing increased mitochondrial biogenesis and upregulation of mitochondrial transcription and translation pathways (39,42,54).…”
Section: Discussionsupporting
confidence: 93%
“…A significant increase in glycolysis may suggest less reliance on or a decrease in mitochondrial respiration. Previous studies have indicated that mitochondria are altered during HCMV infection (25,39,42). We observed that OXPHOS activity was increased in HCMV-infected cells, as measured by the oxygen consumption rate (OCR) using the Seahorse XF e 24 platform ( Fig.…”
Section: Hcmv Infection Of Fibroblasts Results In a Hybrid Glycolysismentioning
confidence: 82%
See 1 more Smart Citation
“…We initially reported the up-regulation of numerous genes with functions in mitochondrial oxidative phosphorylation, fatty acid β-oxidation, and malate-aspartate, ATP, and citrate transport systems in infected fibroblasts at late times pi [53]. Our findings were subsequently confirmed and expanded by a number of studies in fibroblasts and other cell types [101104]. To our knowledge, the current work is the first report showing that a strong transcriptional induction of this type of genes also occurs in myeloid cells and at early times post-entry (Fig 7), making it a hallmark of CMV infection in different cell types and a requirement for successful viral replication.…”
Section: Discussionmentioning
confidence: 66%
“…glycolysis) [21]. Because glycolysis has been shown to be required for efficient replication of viruses including dengue virus, cytomegalovirus, Semliki Forest virus, Sindbis, Adenovirus, and Hepatitis C virus and poliovirus, the Warburg effect may be purposely enhanced by viral infections to increase energy and metabolite production required for virus replication and inhibition of apoptosis in host cells [5, 22, 24, 30, 45, 66]. …”
Section: Discussionmentioning
confidence: 99%